Regulation of financial intermediaries in emerging markets - Ram Mohan, T.T.; Nitsure, Rupa Rege; Joseph, Mathew (New Delhi: Response Books, 2005)
The regulation of financial intermediaries is a significant challenge to policy makers, particularly those in emerging economies. This volume examines: the best practices in regulation in emerging markets; the new Basle norms for capital adequacy; the question of single versus multiple regulators, as viewed by the International Monetary Fund; ways to harness incentives in the context of banking; the subsidy dependence enjoyed by commercial banks and the development of financial institutions before and after the commencement of financial reforms in India; and proposes an innovative approach to setting limits for NPAs in banks.
Some critical issues in the banking sector today -- A primer on finance, growth, and regulation -- A cross-country analysis of external governance and bank profitability -- The regulation of banks in emerging markets: Basel II and the market -- Regulation of financial conglomerates: is unification of financial sector supervision the answer? -- Perspectives on the role of incentives in the prevention of financial crises in emerging economies -- Imperfections in Indian regulation as measured by the Subsidy Dependence Index: A case study of banks and financial institutions -- Nonperforming assets of Indian commercial banks: an analytical exercise
Includes bibliography and index
Keywords: Finance; Market Economy; Economics -- Administration